A prática socioespacial do grafismo e os "lugares de exposição": um olhar sobre a avenida Epitácio Pessoa, João Pessoa/PB - Silva, Akene Shionara Cardoso da (2018)
This research aims to analyze how the socio-spatial practice of graphics in the city of João Pessoa-PB is constituted. Based on research on the origin of contemporary graffiti, demarcating its historical and influential frameworks in Brazil and the world (Chapter 1), to analyze the socio-spatial practice (CARLOS, 2007) of the graphic arts in the city of João Pessoa (Chapter 2), and to understand how the graphics are manifested in the City Landscape, through the spatial cut of Epitacio Pessoa Avenue, considered a "flowing street" (WITCH, 2017) by the "writers" interviewed, in order to understand how the "Places of Exposure "(GOMES, 2013).